Penerapan Metode Talaqqi dalam Menghafal Al-Quran pada Bidang Studi Al-Quran Hadits di Kelas XI IPA 3 MAN 1 Pasaman Barat - Rizka Nurhaliza; Endri Yenti; Jasmienti Jasmienti; Fauzan Fauzan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This research is motivated by the condition of the ability to read and memorize the al-Quran in class XI IPA 3 MAN 1 Pasaman Barat which still needs attention. Especially for students who are still not careful in compiling paragraph by paragraph and are not yet fluent in reading. Therefore, a certain method is needed to overcome this problem. And the talaqqi method is the most appropriate method to overcome this because this method requires a teacher to deal directly with his students to justify reading and provide motivation to his students. This study aims to find out how the application of the Talaqqi Method in memorizing the Koran in class XI IPA 3 MAN 1 Pasaman Barat. These problems are studied using descriptive qualitative research methods that aim to describe and analyze phenomena and events, social activities, attitudes, beliefs, community thoughts individually and in groups with the type of field research (field research). Data collection was carried out using observation techniques, interviews, and also documentation. The key information in this research is the teacher of the hadith recitation and students of class XI IPA 3 MAN 1 Pasaman Barat. Based on the research findings that the researchers conducted, the results obtained were that the application of the Talaqqi Method in memorizing the al-Quran in class XI IPA 3 Man 1 Pasaman Barat was not fully satisfactory and there were still deficiencies.